The State Management Dilemma: BLoC vs. Provider in Modern Flutter Development - Sanghmitra (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
State management is a critical aspect of Flutter application development, directly impacting the efficiency, maintainability and scalability of mobile applications. Among the various state management solutions available in Flutter, BLoC (Business Logic Component) and Provider have emerged as two of the most prominent and widely adopted patterns. This paper presents a comprehensive comparison between BLoC and Provider, analyzing their distinct approaches to managing states, their suitability for different types of applications and their respective strengths and weaknesses. Through an in-depth examination of criteria such as ease of use, learning curve, performance, scalability and community support, this study aims to guide developers in choosing the most appropriate state management solution for their specific project needs. The findings of this research highlight the contexts in which each pattern excels, offering valuable insights for both novice and experienced Flutter developers.